The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000300056
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of carbon nanotubes under external electric fields

Abstract: We study the optical properties of carbon nanotubes within the single-band tight-binding approximation. The great number of one-dimensional-like subbands of the nanotubes lead to typical van Hove singularities on the local density of states. When a tube is under the influence of a laser beam, optical transitions are allowed between Van Hove singularities and they can be observed experimentally in absorption spectra. External magnetic and electric fields modify the energy spectrum of carbon nanotubes inducing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In contrast, the bandgap reduction of the semiconducting part of the junction in Figure is from 0.86 to 0.18 eV when the laser is on. A realistic Stark coefficient of 1.5 eV/(V/nm) 2 for the S 11 state based on the theoretical literature ,, cannot account for the full shift by only the tip electric field. Instead we invoke laser excitation as an additional source of bandgap shift.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the bandgap reduction of the semiconducting part of the junction in Figure is from 0.86 to 0.18 eV when the laser is on. A realistic Stark coefficient of 1.5 eV/(V/nm) 2 for the S 11 state based on the theoretical literature ,, cannot account for the full shift by only the tip electric field. Instead we invoke laser excitation as an additional source of bandgap shift.…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies have predicted that fields on the order of V/nm can induce Stark effects that strongly perturb the electronic structure of semiconducting and metallic carbon nanotubes. 11,17 Such calculations also show how electronic structure varies across a semi-conductingÀmetallic junction. 5 We showed that we can tune the bandgaps of the two halves of a single semiconducting-metallic CNT junction with an applied electric field.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To capture the effect of a QD neighboring the CNT, the onsite energy of each carbon atom in the tight-binding unit cell was modified by the electric potential of the QD at each carbon position . The excited QD was approximated as a point dipole of magnitude μ.…”
Section: Methodsmentioning
confidence: 99%
“…The field is applied perpendicularly to the tube axis, and the intensities are within the range of 10 -2 -10 -1 V/Å, as used in previous calculations. [16][17][18][19][20][21][22][23] The applied field is always parallel to the COOH radical, as shown in Figure 1.…”
Section: Calculation Detailsmentioning
confidence: 99%